Monitoring and study of bio-ecological aspects of the citrus borer, Diploschema rotundicolle (Coleoptera:Cerambycidae), in southern-Uruguay lemon orchards - María Eugenia Amorós; Lautaro Lagarde; Valentina Poloni; Andrés González (Agrociencia Uruguay, 2022)
The citrus borer, Diploschema rotundicolle, is a South American cerambycid beetle considered a primary citrus pest in Uruguay. Serious focalized population explosions have been registered in recent years, particularly in lemon orchards. The larvae feed on the woody tissue, causing tree deterioration and reducing grove productivity and value. Current management relies on cultural control, which is expensive and ineffective partially because of imprecise timing of interventions. Monitoring tools for adults or information of their flight periods in Uruguay are not available thus far. Working in lemon groves in southern Uruguay throughout four flight seasons (2015-2020), we used cross-vane traps coupled with white light devices to capture night-flying adults, and mesh covers around infested trees to study adult emergence. Visual observation of larval activity and oviposition damage were also performed throughout the year. Finally, Eucalyptus globulus windbreaks were checked underneath loosen barks for hidden adults. Throughout all four seasons, adult flight occurred between late January and early April, with a maximum around mid-February. Emergence from mesh-covered trees was observed in the same period. In general, oviposition damage was observed closely after the peak of adult catches. Mostly females were both trapped in light traps and emerged from infested trees. Larval activity was registered all year long. Adults were found sheltered under E. globulus barks; in this case, mostly individual males or couples were found. This study provides a monitoring tool for D. rotundicolle adult flight and information on bio-ecological aspects of this pest in southern Uruguay.